Optimizing the calculation grid for atmospheric dispersion modelling. (April 2015) - Van Thielen, S.; Turcanu, C.; Camps, J.; Keppens, R.
Abstract: This paper presents three approaches to find optimized grids for atmospheric dispersion measurements and calculations in emergency planning. This can be useful for deriving optimal positions for mobile monitoring stations, or help to reduce discretization errors and improve recommendations. Indeed, threshold-based recommendations or conclusions may differ strongly on the shape and size of the grid on which atmospheric dispersion measurements or calculations of pollutants are based. Therefore, relatively sparse grids that retain as much information as possible, are required. The grid optimization procedure proposed here is first demonstrated with a simple Gaussian plume model as adopted in atmospheric dispersion calculations, which provides fast calculations. The optimized grids are compared to the Noodplan grid, currently used for emergency planning in Belgium, and to the exact solution. We then demonstrate how it can be used in more realistic dispersion models. Highlights: Grid points for atmospheric dispersion calculations are optimized. Using heuristics the optimization problem results into different grid shapes. Comparison between optimized models and the Noodplan grid is performed.